Acquisition and consolidation processes following motor imagery practice - Célia Ruffino (Nature Portfolio, 2021)
Abstract It well-known that mental training improves skill performance. Here, we evaluated skill acquisition and consolidation after physical or motor imagery practice, by means of an arm pointing task requiring speed-accuracy trade-off. In the main experiment, we showed a significant enhancement of skill after both practices (72 training trials), with a better acquisition after physical practice. Interestingly, we found a positive impact of the passage of time (+ 6 h post training) on skill consolidation for the motor imagery training only, without any effect of sleep (+ 24 h post training) for none of the interventions. In a control experiment, we matched the gain in skill learning after physical training (new group) with that obtained after motor imagery training (main experiment) to evaluate skill consolidation after the same amount of learning. Skill performance in this control group deteriorated with the passage of time and sleep. In another control experiment, we increased the number of imagined trials (n = 100, new group) to compare the acquisition and consolidation processes of this group with that observed in the motor imagery group of the main experiment. We did not find significant differences between the two groups. These findings suggest that physical and motor imagery practice drive skill learning through different acquisition and consolidation processes.